2022
DOI: 10.1002/jbt.23042
|View full text |Cite
|
Sign up to set email alerts
|

Formononetin attenuates osteoclast differentiation and calcium loss by mediating transcription factor AP‐1 in type I diabetic mice

Abstract: Formononetin (FMN) has been reported as a prospective antiosteoporotic medication. However, the antiosteoporotic properties of FMN are still unclear in a mouse model with diabetes‐induced osteoporosis. An osteoporotic or osteopenic mouse model with type I diabetes mellitus (T1DM) was established using streptozotocin (40 mg/kg) injection for 5 consecutive days. After 12 weeks with FMN intragastric administration (0.5, 5, 20 mg/kg), the antiosteoporotic activity of FMN was evaluated in T1DM mice. FMN supplementa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 39 publications
1
5
0
Order By: Relevance
“…In addition, in an aging society, aging‐related knee injury is a degenerative disease (Roos & Arden, 2016) and often results from other aging‐related diseases (such as diabetes‐induced osteoporosis and atherosclerosis (AS)). FMN has a good therapeutic effect, which was also reported in the existing research results (Jing et al, 2022; Ma et al, 2020). Therefore, FMN has advantages for nontraumatic, particularly aging‐related, degenerative knee injuries and has very good prospects for the treatment of such diseases.…”
Section: Discussionsupporting
confidence: 81%
“…In addition, in an aging society, aging‐related knee injury is a degenerative disease (Roos & Arden, 2016) and often results from other aging‐related diseases (such as diabetes‐induced osteoporosis and atherosclerosis (AS)). FMN has a good therapeutic effect, which was also reported in the existing research results (Jing et al, 2022; Ma et al, 2020). Therefore, FMN has advantages for nontraumatic, particularly aging‐related, degenerative knee injuries and has very good prospects for the treatment of such diseases.…”
Section: Discussionsupporting
confidence: 81%
“…The downstream Fos family proteins (c-Fos, FosB, Fra-1, and Fra-2) form the activating protein-1 (AP-1) complex with the Jun family proteins (c-Jun, JunB, and JunD) and play a key role in osteoclast differentiation ( 54 , 55 ). Together with NFATc1 and other transcription factors, AP-1 can directly induce the expression of a variety of osteoclast-specific genes, such as CTSk , TRAP , and OSCAR , to achieve osteoclast differentiation ( 47 , 56 , 57 ). In our study, we found that MAI treatment decreased the RANKL, CTSK, OSCAR, OCSTAMP, and AP-1 at the gene level, while minimizing the osteoclast expression of the ankle in CIA mice.…”
Section: Discussionmentioning
confidence: 99%
“…Forward, 5′-CACTCCCACCCTGAGATTTGT-3′, Reverse, 5′-CCCCAGAGACATGATGAAGTCA-3′for TRAP; Forward, 5′-CGGGTTTCAACGCCGACTA-3′, Reverse, 5′-TTGGCACTAGAGACGGACAGA-3′for c-Fos; Forward, 5′-GGAGAGTCCGAGAATCGAGAT-3′, Reverse, 5′-TTGCAGCTAGGAAGTACGTCT-3′for Nuclear Factor Of Activated T Cells 1(NFATc1); 10 Forward, 5′-GGACCATCTTTCTGCTCACTCTG-3′, Reverse, 5′-GTTCACTACCTTATTGCCCTCCTG-3′for osteocalcin (OSC); Forward, 5′-CCTTCAAGGTTGTAGCCCTC-3′, Reverse, 5′-GGAGTAGTTCTCATCATTCCCG-3′for Runt-related transcription factor 2 (Runx2); Forward, 5′-TCCATCGAAGAATCAAAGCAGAG-3′, Reverse, 5′-CGAGAGTGTGGAAAGTGTGGAG-3′for Sialoprotein (Sia); Forward, 5′-AGGAGGCACAAAGAAGCCATACG-3′, Reverse, 5′-ATGCCTGCCTTGTACCACGAGC-3′for Osterix (Osx); Forward, 5′-TCATTCCCACGTTTTCACATTC-3′, Reverse, 5′-GTTGTTGTGAGCGTAATCTACC-3′for ALP; Forward, 5′-GTGTGGAGATGTGCCGCTATGAC-3′, Reverse, 5′-AGTCTCGGAGGTGCTCTTCAGTG-3′for JAK2; Forward, 5′-TGTCAGATCACATGGGCTAAAT-3′, Reverse, 5′-GGTCGATGATATTGTCTAGCCA-3′for STAT3; Forward, 5′-CGCTCTTCTGTCTACTGAACTTCGG-3′, https://doi.org/10.2147/IJN.S413692…”
Section: Real-time Quantitative Reverse Polymerase Chain Reaction (Qr...mentioning
confidence: 99%
“…The exosomes incorporate, transfer, stabilize, and protect themselves from degradation. [10][11][12] Lv et al 13 found that miR-181b-5p delivered by osteocyte-derived exosomes promotes human periodontal ligament stem cell proliferation via the phosphatase and tensin homolog(PTEN)/protein kinase B(PKB) pathway, suggesting that miRNAcarrying exosomes are crucial for bone remodeling in periodontitis. 14,15 Hu et al 3 illustrated that sympathetic neuro-stress could drive osteoblastic exosomal miR-21 transfer to regulate osteoclastogenesis.…”
Section: Introductionmentioning
confidence: 99%